2018
DOI: 10.12659/msm.910754
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic and Outcome Prediction Value of Transthoracic Impedance Cardiography in Heart Failure Patients During Heart Failure Flare-Ups

Abstract: BackgroundThis study aimed at evaluating the diagnostic and outcome prediction value of transthoracic impedance cardiography (ICG) in heart failure (HF) patients admitted for in-hospital treatment due to flare-ups of their condition.Material/MethodsIn total, 120 patients of intensive care units who were admitted due to HF flare-ups were involved to the study. The findings of ICG were compared to data obtained by other methods used for diagnosing HF.ResultsStatistically significant (p<0.001) results were obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 23 publications
1
9
0
2
Order By: Relevance
“…Emerging studies have demonstrated the correlation of STR and risk of death in patients with HF. Sadauskas et al reported that STR ≥ 0.55 is an indicator of higher risk to death in 6 months in patients with recurrent HF (OR = 0.29) ( 37 ). Moreover, in PREDICT trial, a multicenter trial including 2,316 patients, the hemodynamic parameters including STR were identified as a predictor of short-term clinical events, such as HF recurrent decompensation ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…Emerging studies have demonstrated the correlation of STR and risk of death in patients with HF. Sadauskas et al reported that STR ≥ 0.55 is an indicator of higher risk to death in 6 months in patients with recurrent HF (OR = 0.29) ( 37 ). Moreover, in PREDICT trial, a multicenter trial including 2,316 patients, the hemodynamic parameters including STR were identified as a predictor of short-term clinical events, such as HF recurrent decompensation ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…ICG parameters were recorded immediately after TTE, using a Niccomo™ transthoracic ICG monitor (Medis Medizinische Messtechnik GmbH, Ilmenau, Germany) [20] and on the last day of patient's in-hospital treatment, except if there was a death during the hospitalization period. All ICG parameters were recorded, although we only evaluated the main parameters, suitable for the diagnosis and prognosis of HF: systolic index, TFC, cardiac output, TFCI, systolic time ratio, left cardiac work, and left cardiac work index [9][10][11]17].…”
Section: Methods Of Examinationmentioning
confidence: 99%
“…However, other researchers found only a modest correlation between invasively measured cardiac output and cardiac output measured during ICG (r=0.4 to 0.6 on serial measurements) [ 13 ]. In our previous research, we also found only a weak correlation between BNP and cardiac output measured during ICG (r=−0.23, P =0.012) [ 11 ]. ICG parameters have also been extensively researched as possible prognostic indicators in patients with HF.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…For example, when monitoring patients with heart failure, ICG data that included cardiac output (CO), the systolic time ratio (STR) were found to correlate with the left ventricular ejection fraction (LVEF) [11]. A significant association between ICG data and CO have also been shown [12]. previously published studies have shown a significant correlation between LVEF and STR [13,14].…”
Section: Introductionmentioning
confidence: 99%